Very Low Dose Amitriptyline for Clozapine-Associated Sialorrhea - Sinha, Siddhartha; Simlai, Jayati; K. Praharaj, Samir (Current Drug Safety, 2016)
Clozapine is an antipsychotic drug recommended for resistant schizophrenia, but its widespread use is limited by adverse effects. Sialorrhea is a common and troublesome adverse effect seen with clozapine which leads to poor compliance. Several treatment strategies are advocated, no single treatment is considered superior. Amitriptyline, a tricyclic antidepressant, has been found to be useful for clozapine-associated sialorrhea at 87–100 mg per day. We report the effect of very low dose amitriptyline (10 mg per day) in a patient with clozapine-associated sialorrhea. There was rapid and complete resolution of sialorrhea after three days without any emergent adverse effect.
Keywords: sialorrhea